Cognitive Computing with IBM Watson - High, Rob (Packt Publishing, 2019)
Understand, design, and create cognitive applications using Watson's suite of APIs Key Features Work with IBM Watson APIs to build efficient and powerful cognitive apps Build smart apps to carry out different sets of activities with the help of real-world use cases Get well-versed with the best practices of IBM Watson and implement them in your daily work Book Description Cognitive computing is rapidly becoming a part of every aspect of our lives through data science, machine learning (ML), and artificial intelligence (AI). It allows computing systems to learn and keep on improving as the amount of data in the system increases. This book introduces you to a whole new paradigm of computing - a paradigm that is totally different from the conventional computing of the Information Age. You will learn the concepts of ML, deep learning (DL), neural networks, and AI with the help of IBM Watson APIs. This book will help you build your own applications to understand, and solve problems, and analyze them as per your needs. You will explore various domains of cognitive computing, such as NLP, voice processing, computer vision, emotion analytics, and conversational systems. Equipped with the knowledge of machine learning concepts, how computers do their magic, and the applications of these concepts, you'll be able to research and apply cognitive computing in your projects. What you will learn Get well-versed with the APIs provided by IBM Watson on IBM Cloud Understand ML, AI, cognitive computing, and neural network principles Implement smart applications in fields such as healthcare, entertainment, security, and more Explore unstructured data using cognitive metadata with the help of Natural Language Understanding Discover the capabilities of IBM Watson's APIs by using them to create real-life applications Delve into various domains of cognitive computing, such as media analytics, embedded deep learning, computer vision, and more Who this book is for If you're new to cognitive computing, you'll find this book useful. Although not a prerequisite, some knowledge of artificial intelligence and deep learning will be an added advantage. This book covers these concepts using IBM Watson's tools. Downloading the example code for this ebook: You can download the example code files for this ebook on GitHub at the following link: https://github.com/PacktPublishing/Cognitive-Computing-with-IBM-Watson . If you require support please email: customercare@packt.com.